Advancements in the use of cancer nanovaccines: Comprehensive insights with focus on lung and colon cancer - Qian Li; Shi Jingjuan; Pei Chang; Hu Jian; Han Wen; Yu Le; Chu Hanguang (Nanotechnology Reviews)
Cancer remains a prima facie cause of morbidity and mortality globally, necessitating efficient medicaments. The inter-mechanisms between immune system cascade and the ability of cancer cells to evade immunological responses pose a significant challenge in developing effective cancer treatments despite advanced immunotherapy treatments. Intervention of nanotechnology in developing vaccine is the area of interest now and therefore, we have summarized the recent developments in cancer nanovaccine. The article provides a comprehensive review of available vaccine treatment for cancer and also nanovaccine usages especially for non-small cell lung cancer and colon cancer, emphasizing on their development, mechanisms of action, and diverse range of health applications. The article highlights different types of nanocarriers, such as protein-based carriers, liposomes, polymers, and exosomes, which in-turn act to deliver tumor antigens, adjuvants, or immunomodulatory agents directly to targeted sites and their effectiveness in improving cancer immunotherapy. The recent promising innovations in cancer nanovaccine technology, viz., immunotherapeutic nanovaccines, stimulator of interferon genes agonist-based vaccines, and nanogel supporting photo thermal therapy have also been addressed in detail. The article also summarizes the importance of biocompatibility and specificity as a criterion in minimizing adverse effects by including the global impact of nanovaccines in reducing cancer recurrence.